Strengthening Student Character through Akidah Akhlak Lessons at Madrasah Diniyah Tarbiyatus Sibyan Pamekasan - Andri Sutrisno; Fitrah Sugiarto; Fajriyah Fajriyah (Jurnal Kawakib, 2022)
Education becomes an essential part of the lives of students, especially in character education. Because character education will be the ultimate goal desired by teachers and their parents at home, so it is necessary to strengthen character education in schools tarbiyatus sibyan, especially in diniyah madrasahs that teach Islamic sciences. In Pamekasan there is a diniyah madrasa called tarbiyatus sibyan by always strengthens character education for its students by strengthening the lessons of moral creeds in theoretical and practical forms. So this will make the students have commendable traits and behaviors. One of the methods used in this study is field qualitative research with the type of case study research. Where researchers carry out 3 data collection techniques, observation, interviews and documentation while the data analysis techniques use data reduction, data presentation, drawing conclusions and data verification. So this study presents the findings of the study; the first result, Strengthening character education through moral academia lessons in the formation, transformation, transmission and development of the potential of the learners. The Second result, Implementation of strengthening character education through Akidah akhlak lessons through congregational prayer activities, learning the yellow book and exemplary attitudes and habituation to students.